Heterostructure of 2D CoP Nanosheets/1D Carbon Nanotubes to Significantly Boost the Alkaline Hydrogen Evolution. Issue 2 (12th December 2019) - Zhang, Yu; Wang, Yong; Wang, Tingting; Wu, Niandu; Wang, Yuanqi; Sun, Yuan; Fu, Lin; Du, Youwei; Zhong, Wei
Abstract: The enhancement of catalytic performance of cobalt phosphide‐based catalysts is highly desirable but still challenging to replace noble metal for the hydrogen evolution reaction (HER) in alkaline. Here, a unique hetero‐nanostructure of CoP nanosheets (CoP NS) grafted by carbon nanotubes (CNTs) is reported. As analyzed and discussed, the well‐maintained open porous CoP nanosheets structure and abundant active interfaces between CNTs and CoP NS at the CoP NS/CNTs catalyst, together with enlarged catalytic active sites, reduce HER reaction energy barrier, increase charge transfer rate offered by the hybrid porous structure, and contribute to the extraordinary water reduction performance. Furthermore, the wettability of CoP NS/CNTs is also enhanced relative to CoP NS. Consequently, this CoP NS/CNTs unique hetero‐nanostructure shows significantly high‐efficiency HER activity in 1.0 m KOH electrolyte with negligible onset overpotential, a small overpotential of 68 mV at −10 mA cm −2, a low Tafel slope of 57 mV dec −1, and stability of up to 24 h, which is among the best reported values for CoP‐based HER electrocatalysts in alkaline media to date. This study provides an insight into rational design and low‐cost synthesis of the non‐precious‐based electrocatalysts based on interfaces and wettability with high efficiency and stability for HER. Abstract : Cobalt phosphide nanosheets grafted by carbon nanotubes (CoP NS/CNTs) are used for the hydrogen evolution reaction (HER) in which CNTs function to increase hydrophilicity and transfer electrons to the CoP NS active sites. The CoP NS/CNTs exhibit excellent HER performance under an alkaline condition through great interfacial construction and enhanced hydrophilic synergistic effects. Meanwhile, the porous structure on the CoP nanosheets also provides more active sites for enhancing HER.